A comprehensive error analysis of the planetary roller screw mechanism. (May 2022) - Ma, Shangjun; Wu, Guanyu; Zhang, Jianxin; Deng, Wenzhu; Xie, Lizhong; Zhou, Yong
To reveal the error generation, transmission, and accumulation process, a comprehensive error analysis model is proposed in this paper; furthermore, the model is used to determine the influence on the transmission error and the error sensitivity of a planetary roller screw mechanism (PRSM). After error source analysis, the differential error vector and matrix are used to express the small errors because the magnitude of all errors in the PRSM is relatively small. To comprehensively consider the error coupling relationship between thread structure errors and gear structure errors, error flow models of the PRSM components are established. On this foundation, transmission error characterization model and error sensitivity evaluation model are also established. Finally, error values and transmission error are measured, and the sensitivity of each error to the transmission error is calculated. The results show that the transmission error is periodic and fluctuate with screw rotation. The component eccentric errors, pitch errors, and thread clearance have obvious influence on the transmission error, so they should be limited emphatically.